ANALISIS PENGARUH INVESTMENT OPPORTUNITY SET, FREE CASH FLOW, RETURN ON ASSET, FIRM SIZE, DEBT TO EQUITY RATIO TERHADAP DIVIDEND PAYOUT RATIO (Studi pada Perusahaan Sektor Keuangan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2012-2016) - Rara Ayu Ratnasari (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
This research was conducted to examine the effect of Investment Opportunity Set, Free Cash Flow, Return On Asset, Firm Size, Debt To Equity Ratio to Dividend Payout Ratio in Financial Sector Companies listed in Indonesia Stock Exchange (IDX) Period 2012-2016. Sampling technique was taken by purposive sampling method. The data were obtained based on the publication of Indonesian Capital Market Directory (ICMD 2017). Obtained a number of samples of 34 companies from 91 companies of the financial sector listed on the Indonesia Stock Exchange 2012-2016. The analysistechnique used is multiple linear regression with the least squares equation and the classical assumption test. Hypothesis test was using f-statistic to test the influence between variables simultaneously and t-statistic to test the partial regression coefficient with 5% confidence level. The results showed that the research data is normally distributed and there is no deviation of classical assumption, it means that the available data have been qualified to use multiple linear regression equation model. Simultaneous analysis result shows that IOS, FCF, ROA, SIZE and DER have an effect on DPR. Partial analysis result show that ROA have a significant positive effect, DER have negative significant effect because the value of significance both < 0,05 whereas IOS, FCF and SIZE have no effect against DPR.